KONSEP DIRI WARGA BELAJAR PROGRAM KESETARAAN DI PKBM PELITA RIAU, KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Shinta Aprila Sari; Sumardi '; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research are: 1) To know the level of self-understanding of citizens learning equality program, 2) To know the level of self-feelings of citizens learning equality program, 3) To know the level of self-view of citizens learning equality program, 4) to know the level of self-confidence (5) To know whether there is a difference between the self-concept of packet A, packet B, and package C, and 7) To know the contribution / contribution of age factor, gender , Religion, ethnicity, family type, and social class in shaping the concept of self-learned citizens. The type of research used in this research is descriptive research with quantitative approach. The variables in this study are self-concept of citizens learning equality program, and without connecting with other variables. Selanjutanya used indicators adopted from several opinions of experts, including: 1. Self-understanding, 2. Feelings, 3. Self-views, and 4. Confidence. This research was conducted at CLC Pelita Riau, Rumbai Pesisir Sub-district, Pekanbaru City, involving 55 residents studying equality program from Package A, Package B, and Package C as research sample. Data collection technique used in this research is using questionnaire with scale Measurements are: Strongly Agree (SS), Agree (S), Doubt (RR), Disagree (TS), and Strongly Disagree (STS). The analysis used in this research are: 1) Descriptive Statistics, with Mean and SD, and Percentage, 2) Inferential statistics, using ANOVA analysis.Keywords: Self Concept, Student Learning, Equality Program, PKBM Pelita Riau